FAILURE ANALYSIS AND IMPROVEMENT OF AN SUPPORT FRAME FOR INDEPENDENT SUSPENSION - YAN HuiDong; LI HongBiao (Jixie qiangdu)
one support frame was designed for the independent suspension of 8 × 8 off road chassis,on purpose of that connect two suspension brackets. The frame was damaged after vehicle enhance road test with the weld seam cracked and the bolt cut off. According to the failure performance,the model about independent suspension included support frame was built for failure analysis,and the failure was caused by uncoordinated deformation of different parts; the support frame is improved and verified by simulation and test.